Tanggung Jawab Hukum Penyedia Jasa Apabila Terjadi Kecelakaan Kerja pada Pekerjaan Konstruksi - Mahardhika, Guruh; Khairani, Khairani; Hasbi, Muhammad (Nagari Law Review, 2024)
The recent increase in the number of construction accidents, whether caused by process errors or circumstances beyond human control, leaves problems related to the quality and responsibility of providers and users. Aspects of the responsibility of Service Providers need to be emphasized and the regulations must provide guarantees of legal certainty. This thesis focuses on a implementations of RKK Documents created by Service Providers when bidding for construction work. Problems in the research include how to implement and monitor the RKK Document on works of “Penanganan Lereng Ruas Tambu-Tompe-Pantoloan” and what is the form of the Service Provider's legal responsibility if a construction accident occurs. The research sample is works of “Penanganan Lereng Ruas Tambu-Tompe-Pantoloan”, the project which is carried out by PT. Anugerah Karya Agra Sentosa. The party that is the service user for this project is BPJN Sulteng Ministry of PUPR. The method used in this research is juridical-empirical, which focuses on collecting empirical data in the field. The theories used in this research are the theory of legal certainty, the theory of legal awareness, and the theory of legal effectiveness. The data used in this research are primary data and secondary data. Primary data comes from interviews with several parties, including the Directorate of Construction Sustainability of the Ministry of PUPR and Commitment Making Officials (PPK). Meanwhile, secondary legal material in this research includes regulations related to K4 and SMKK standards, the main ones are the 1945 Constitution, Law Number 2 of 2017 concerning Construction Services, and PUPR Ministerial Regulation Number 10 of 2021 concerning Guidelines for Construction Safety Management Systems . The research results show that in the application of the RKK document to the work on handling the slopes of the Tambu-Tompe-Pantoloan section, there are several discrepancies. Firstly, the Service Provider was proven to have used substitute workers who did not have competence in the form of a Work Competency Certificate, which caused construction accidents. Second, the Service Provider does not comply with Standard Operating Procedures when replacing Occupational Safety Experts.